Panta Rhei 2013–2015: global perspectives on hydrology, society and change. Issue 7 (18th May 2016) - McMillan, Hilary; Montanari, Alberto; Cudennec, Christophe; Savenije, Hubert; Kreibich, Heidi; Krueger, Tobias; Liu, Junguo; Mejia, Alfonso; Van Loon, Anne; Aksoy, Hafzullah; Di Baldassarre, Giuliano; Huang, Yan; et al.
ABSTRACT: In 2013, the International Association of Hydrological Sciences (IAHS) launched the hydrological decade 2013–2022 with the theme "Panta Rhei: Change in Hydrology and Society". The decade recognizes the urgency of hydrological research to understand and predict the interactions of society and water, to support sustainable water resource use under changing climatic and environmental conditions. This paper reports on the first Panta Rhei biennium 2013–2015, providing a comprehensive resource that describes the scope and direction of Panta Rhei. We bring together the knowledge of all the Panta Rhei working groups, to summarize the most pressing research questions and how the hydrological community is progressing towards those goals. We draw out interconnections between different strands of research, and reflect on the need to take a global view on hydrology in the current era of human impacts and environmental change. Finally, we look back to the six driving science questions identified at the outset of Panta Rhei, to quantify progress towards those aims.Editor D. Koutsoyiannis;Associate editor not assigned